Microorganisms that are critical for the fermentation quality of paper mulberry silage. (15th June 2021) - Guo, Linna; Wang, Xuekai; Lin, Yanli; Yang, Xueping; Ni, Kuikui; Yang, Fuyu
Abstract: Silage quality remains an important issue in farming, as do limitations in the range of products suitable for animal fodder. We therefore explored the microorganisms that are critical for the fermentation quality of paper mulberry silage. Low (unwilted) and high (wilted) dry matter (DM) paper mulberry were harvested at two cutting times. These were ensiled for 0, 3, 7, 14, and 56 days, respectively. Compared with unwilted silages, wilting significantly decreased ( p  < 0.05) silage pH value, ammonia‐N concentration, and yeast counts but increased ( p  < 0.05) lactic acid content. In addition, higher ( p  < 0.05) crude protein (CP) contents were also observed in wilted silages. Next‐generation sequencing (NGS) analysis revealed that wilting reduced the abundance of Enterobacter, while increasing that of Lactobacillus . Single‐molecule real‐time sequencing (SMRT) revealed that the silage was enriched in the lactic acid bacteria (LAB), Lactobacillus rhamnosus after wilting, which showed a positive correlation with CP and lactic acid content. We conclude that wilting may help preserve paper mulberry silage, facilitating its use as a new fodder resource. Moreover, L .  rhamnosus has the potential to be developed as a new inoculant for the modulation in wilted silages, particularly paper mulberry silage. Abstract : Bacterial community was analyzed by combination of NGS and SMRT sequencing. Wilting enriched the abundance of Lactobacillus rhamnosus . Lactobacillus rhamnosus was the critical species showing the most positively correlation with wilted silage quality, and have the potential to be developed as new silage inoculant.